Compensation Strategies for Gait Impairments in Parkinson Disease: A Review - Nonnekes, Jorik; Ružicka, Evžen; Nieuwboer, Alice; Hallett, Mark; Fasano, Alfonso; Bloem, Bastiaan R (JAMA Neurology, 2019)
Importance: Patients with Parkinson disease can use a wide variety of strategies to compensate for their gait impairments. Examples include walking while rhythmically bouncing a ball, crossing the legs when walking, or stepping over an inverted cane. An overview and classification of the many available compensation strategies may contribute to understanding their underlying mechanisms and developing focused rehabilitation techniques. Moreover, a comprehensive summary of compensation strategies may help patients by allowing them to select a strategy that best matches their needs and preferences and health care professionals by permitting them to incorporate these into their therapeutic arsenal. To create this overview, this narrative review discusses collected video recordings of patients who spontaneously informed clinicians about the use of self-invented tricks and aids to improve their mobility. Observations: Fifty-nine unique compensation strategies were identified from approximately several hundred videos. Here, these observed strategies are classified into 7 main categories for elaboration on their possible underlying mechanisms. The overarching working mechanisms involve an allocation of attention to gait, the introduction of goal directedness, and the use of motor programs that are less automatized than those used for normal walking. Conclusions and Relevance: Overall, these compensation strategies seem to appeal to processes that refer to earlier phases of the motor learning process rather than to a reliance on final consolidation. This review discusses the implications of the various compensation strategies for the management of gait impairment in Parkinson disease.
Keywords: Self-Management; Gait Disorders, Neurologic; Parkinsonova nemoc; Humans; neurologické poruchy chůze; self-management; lidé; Parkinson Disease